2019
DOI: 10.1177/1120672119858895
|View full text |Cite
|
Sign up to set email alerts
|

Acute angle-closure glaucoma with choroidal effusion revealing a hantavirus infection: Description of ultrasound biomicroscopy imagery and optical coherence tomography Visante

Abstract: Purpose: To report a case of bilateral angle-closure associated with systemic hantavirus infection. Materials and methods: A 32-year-old Caucasian man was referred with blurred vision, fever, cough, dyspnea and thrombocytopenia. Ophthalmologic examination revealed myopic shift, elevated intraocular pressure (30 mmHg right eye and 24 mmHg left eye), corneal edema, iridocorneal angle closure and shallow anterior chamber. Ciliochoroidal effusion was detected on anterior segment optical coherence tomography and ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Kontkanen and Puustjärvi have also reported conjunctival hemorrhages in the case of one female patient with NE [46]. Conjunctival chemosis was noted to some extent in 87% of the eyes in a previous prospective study, in which only one patient suffered bilateral subconjunctival bleeding [4,49]. The acute phase of NE causes an increase in tissue permeability and interstitial hemorrhages.…”
Section: Eyelid and Conjunctival Changesmentioning
confidence: 86%
See 2 more Smart Citations
“…Kontkanen and Puustjärvi have also reported conjunctival hemorrhages in the case of one female patient with NE [46]. Conjunctival chemosis was noted to some extent in 87% of the eyes in a previous prospective study, in which only one patient suffered bilateral subconjunctival bleeding [4,49]. The acute phase of NE causes an increase in tissue permeability and interstitial hemorrhages.…”
Section: Eyelid and Conjunctival Changesmentioning
confidence: 86%
“…Contradictory results of IOP level in patients with NE have been published previously [4,[37][38][39][43][44][45]47,48]. There are some case reports of acute glaucoma attacks associated with NE [37][38][39][48][49][50] and several reports of decreased IOP during the acute phase of NE [4,43,45]. Cho et al have reported a single case of bilateral acute angle-closure glaucoma in Korean hemorrhagic fever, a very severe form of HFRS caused by the Hantaan virus [48].…”
Section: Intraocular Pressure (Iop) In Nementioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, previous studies have suggested that COVID-19 infection-related adverse behavior Considering the strong association between testing positive for COVID-19 and developing AACG, we hypothesized that COVID-19 may afect the function of the angle, leading to glaucoma onset. Previous studies have indicated that viral infections can trigger AACG [31,32]. Infections such as Vogt-Koyanagi-Harada syndrome and human immunodefciency virus infection are more likely to induce AACG, and Hantavirus infection specifcally causes acute binocular angle-closure glaucoma, possibly mediated by choroidal leakage [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism is unclear, but the leading theory involves an anterior shift of the lens due to underlying inflammation of the ciliary body [91]. Anterior shift of the lens may predispose to angle closure glaucoma, reported in exceptional cases, and may be associated with ciliochoroidal effusion [89,92]. In the largest case series (46 patients) to date reporting on ocular involvement in patients who had recovered from acute HFRS, 70% reported ocular symptoms during the disease course, which were often bilateral [93].…”
Section: Rift Valley Fever (Rvf)* (Phenuiviridae)mentioning
confidence: 99%